Microsatellite analysis reveals low genetic diversity in managed populations of the critically endangered gharial (Gavialis gangeticus) in India - Sharma, Surya Prasad (Sci Rep, 2021)
The gharial (Gavialis gangeticus) is a critically endangered crocodylian, endemic to the Indian subcontinent. The species has experienced severe population decline during the twentieth century owing to habitat loss, poaching, and mortalities in passive fishing. Its extant populations have largely recovered through translocation programmes initiated in 1975. Understanding the genetic status of these populations is crucial for evaluating the effectiveness of the ongoing conservation efforts. This study assessed the genetic diversity, population structure, and evidence of genetic bottlenecks of the two managed populations inhabiting the Chambal and Girwa Rivers, which hold nearly 80% of the global gharial populations. We used seven polymorphic nuclear microsatellite loci and a 520 bp partial fragment of the mitochondrial control region (CR). The overall mean allelic richness (Ar) was 2.80 ± 0.40, and the observed (Ho) and expected (He) heterozygosities were 0.40 ± 0.05 and 0.39 ± 0.05, respectively. We observed low levels of genetic differentiation between populations (F(ST) = 0.039, P < 0.05; G’(ST) = 0.058, P < 0.05 Jost’s D = 0.016, P < 0.05). The bottleneck analysis using the M ratio (Chambal = 0.31 ± 0.06; Girwa = 0.41 ± 0.12) suggested the presence of a genetic bottleneck in both populations. The mitochondrial CR also showed a low level of variation, with two haplotypes observed in the Girwa population. This study highlights the low level of genetic diversity in the two largest managed gharial populations in the wild. Hence, it is recommended to assess the genetic status of extant wild and captive gharial populations for planning future translocation programmes to ensure long-term survival in the wild.